Attitude of Romanian Medical Students and Doctors toward Business Ethics: Analyzing the Influence of Sex, Age, and Ethics Education - George-Dumitru Constantin; Crisanta-Alina Mazilescu; Teodora Hoinoiu; Bogdan Hoinoiu; Ruxandra Elena Luca; Loredana-Ileana Viscu; Ioana Giorgiana Pasca; Roxana Oancea (MDPI AG, 2023)
This study investigated the attitude of Romanian medical students and doctors toward business ethics by measuring the preference for a particular ethical philosophy, namely, the preference for Machiavellianism, moral objectivism, social Darwinism, ethical relativism, and legalism. At the same time, this study aimed to explore the influence of sex, age, and ethics education on the attitude toward business ethics. The data collection was performed using a voluntary self-administered online survey including the Attitudes Toward Business Ethics Questionnaire (ATBEQ) instrument. Our findings show that the values based on which Romanian medical students and doctors make business decisions belong predominantly to the moral objectivism philosophy, which is grounded on rational actions based on a set of objective moral standards.